Enhancing teachers’ digital literacy for security: a systematic review of frameworks and analytical methods in education - Othman, Nadirah; Sarkam, Nor Aslily; Baharun, Norhayati; Hoon, Teoh Sian; Masrom, Suraya; Mohamad Razi, Nor Faezah; Abd Rahman, Abdullah Sani (Institute of Advanced Engineering and Science, 2025)
The rising use of digital tools in education emphasizes the crucial need of teachers’ digital security, which relies on strong digital literacy. This study assesses teachers’ digital literacy on digital security literature to meet the urgent need for safe practices in schools due to increased security breaches. A total of 30 studies were reviewed using preferred reporting items for systematic reviews and meta-analyses (PRISMA) criteria to build frameworks and data analysis methodologies in this field. Five research areas were identified: teacher perspectives, security-related issues, educational impacts, pedagogical approaches, and instrument validation. The predominant framework used was the digital competence framework for citizens (DigComp), however hybrid frameworks that integrate other theoretical perspectives were highly commended for their comprehensive approach. The 30% of the studies focused on security issues, including cyberbullying and data protection, while 70% incorporated security dimensions into digital literacy frameworks. Quantitative approaches comprising 60%, including t-tests, analysis of variance (ANOVA), and regression analysis. Structural equation modeling (SEM) was used in several studies to examine complex relationships. Although current research predominantly emphasizes quantitative methods, future investigations could enhance knowledge of teachers’ digital literacy and security by integrating SEM with artificial neural networks (ANN). This review emphasizes the necessity for hybrid frameworks and sophisticated approaches to enhance research.